ANALISIS KESALAHAN PENGGUNAAN TENSES DALAM KALIMAT BAHASA INGGRIS OLEH SISWA SEKOLAH DASAR - Cristian Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the misuse of tenses in English sentences by students at SDN Pangarangan V, as well as to explore the causes of these errors and the strategies students use to overcome them. The method used in this study is qualitative research with a case study approach, involving in-depth interviews with 15 students from grades 5 and 6, as well as analysis of their written documents. The research findings indicate that the most frequent errors occur in the use of the simple past tense, simple present tense, and future tenses. These errors are primarily caused by language transfer, where students transfer rules from the Indonesian language, which does not have a tense system, into English, as well as a lack of understanding of the concept of time taught in English. Additionally, students find it difficult to differentiate between the use of different tenses, such as the simple past tense and the present perfect tense, and often misuse verbs after the auxiliary verb